Global Citizenship Education Critical and International Perspectives - Akkari, Abdeljalil; Maleq, Kathrine (Springer International Publishing : Imprint: Springer, 2020)
This open access book takes a critical and international perspective to the mainstreaming of the Global Citizenship Concept and analyses the key issues regarding global citizenship education across the world. In that respect, it addresses a pressing need to provide further conceptual input and to open global citizenship agendas to diversity and indigeneity. Social and political changes brought by globalisation, migration and technological advances of the 21st century have generated a rise in the popularity of the utopian and philosophical idea of global citizenship. In response to the challenges of today's globalised and interconnected world, such as inequality, human rights violations and poverty, global citizenship education has been invoked as a means of preparing youth for an inclusive and sustainable world. In recent years, the development of global citizenship education and the building of students' global citizenship competencies have become a focal pointin global agendas for education, international educational assessments and international organisations. However, the concept of global citizenship education still remains highly contested and subject to multiple interpretations, and its operationalisation in national educational policies proves to be challenging. This volume aims to contribute to the debate, question the relevancy of global citizenship education's policy objectives and to enhance understanding of local perspectives, ideologies, conceptions and issues related to citizenship education on a local, national and global level. To this end, the book provides a comprehensive and geographically based overview of the challenges citizenship education faces in a rapidly changing global world through the lens of diversity and inclusiveness.